Desain dan Implementasi Sistem Navigasi pada Automated Guided Vehicle (AGV) - Fakih Irsyadi; Dinar Nugroho Pratomo; Sugeng Julianto; Muhammad Shofuwan Anwar; Alfonzo Aruga Paripurna Barus (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2021)
This research aims to build mechanical system of Automated Guided Vehicle (AGV) and navigation system for AGV.  The navigation system consists of RFID reader and rotary encoder. The testing result show that mechanical system of AGV was successfully finished. There is a mechanical problem on drive system of AGV. Each part of navigation system works well according to design. Line sensor can be used for path detection with the given threshold values. Encoder can be used to measure the speed of AGV with the maximum error accuracy less than 2 rpm. This result shows that every part of AGV is ready to run localization and navigation algorithm, even though, it needs to do some improvement on driving parts.